Regenerating the heart Stem Cells and the Cardiovascular System - Cohen, Ira S. (Stem Cell Biology and Regenerative Medicine, 2011)
Medical research made huge strides in treating heart disease in the 20th century, from drug-eluding stents to automatic internal defibrillators. Public awareness of the dangers of heart disease has never been more pervasive. Now, though, ten years into a new millennium, scientists are gearing up for the next great challenges in tackling this pervasive condition. Cell therapy is going to be a key weapon in the fight against heart disease. It has the potential to address many cardiovascular conditions. From heart failure to atrioventricular nodal dysfunction, the young but promising field of cell therapy is set to play a significant role in developing the cures that the upcoming decades of hard work will yield. Regenerating the Heart: Stem Cells and the Cardiovascular System organizes the field into a digestible body of knowledge. Its four sections cover mechanical regeneration, electrical regeneration, cardiac tissues and in vivo stem cell therapies. An array of talented researchers share the fruits of their labors, with chapters covering such crucial issues as the cardiogenic potential of varying stem cell types, the ways in which they might be used to tackle arrhythmias, their possible application to biological replacements for cardiac tissues such as valves, and the varying approaches used in the in vivo evaluation of stem cell therapies, including methods of delivering stem cells to the myocardium. This comprehensive survey of an area of research with such exciting potential is an invaluable resource both for veteran stem cell researchers who need to monitor fresh developments, and for newly minted investigators seeking inspirational example